Structure and timing of Neoarchean gold mineralization in the Southern Cross district (Yilgarn Craton, Western Australia) suggest leading role of late Low-Ca I-type granite intrusions - Doublier, M.; Thebaud, N.; Wingate, M.; Romano, S.; Kirkland, C.; Gessner, K.; Mole, D.; Evans, Noreen (Pergamon-Elsevier Science Ltd., 2014)
The formation of structurally controlled lode-gold deposits is a controversial subject with both magmatic and metamorphic fluids considered a feasible source for gold. Here we present a study from the Southern Cross district (Yilgarn Craton, Western Australia), where structurally controlled Neoarchean gold deposits are hosted in amphibolite facies greenstones. We combine geochronological data with structural analysis to constrain the timing and structural control of ore deposition. We show that gold mineralization took place between c. 2638 and 2630 Ma, contemporaneous with the onset of voluminous intrusions of Low-Ca, I-type granites, which are ubiquitous in Southern Cross and elsewhere in the Yilgarn Craton. We argue that the timing of the intrusions, their spatial association with gold deposits, their chemical composition, and isotopic signature are consistent with Low-Ca granites being a major fluid source for mineralization. We propose that the fluid release by cooling plutons was facilitated by transport along active amphibolite facies shear zones. As gold mineralization was synchronous with Low-Ca magmatism across large areas of the Yilgarn Craton, our model may be applicable to orogenic gold deposits in other parts of the Yilgarn Craton as well as other Archean granite-greenstone terrains with a ‘late granite bloom'.